Effects of fungal volatile organic compounds on Arabidopsis thaliana growth and gene expression. (February 2019) - Lee, Samantha; Behringer, Gregory; Hung, Richard; Bennett, Joan
Abstract: Many microorganisms produce volatile organic compounds (VOCs) with biological effects on plants. In this study, Arabidopsis seeds or 14-day-old vegetative plants were exposed to 0.5 μg/l of chemical standards of 26 VOCs previously identified from the biocontrol fungus Trichoderma . Seven compounds (1-decene, 2-heptylfuran, 2-methyl-1-propanol, 2-methyl-1-butanol, 3-methyl-1- butanol, 2-heptanone, and 1-octen-3-ol) were further tested at the physiological concentration (10 ng/l) and 3-methyl-1-butanol, 1-decene, and 2-heptylfuran induced significant increases in fresh weight and total chlorophyll content. Plants exposed to 1-decene had the greatest increase in plant fresh shoot weight (38.9%) and chlorophyll content (67.8%). An RNA sequencing analysis was performed on plants treated with vapors of 1-decene. The expression of 123 genes was differentially affected, encompassing genes involved in cell wall modification, auxin induction, stress, and defense responses, with several major classes of stress-related genes showing down-regulation. To our knowledge, this is the first report of the effect of a plant growth promoting VOC on gene expression in Arabidopsis thaliana . As the role of fungal VOCs in biocontrol moves from correlative studies to more hypothesis driven approaches, our findings can guide both basic and applied studies in agricultural research.